WORDS THAT BECOME NORMS IN A LANGUAGE DUE TO THEIR INFORMATIVENESS - Madina Rzayeva Aliaqa, (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
The use of international terms in press language is driven more by the need to convey new information than by strict lexical-semantic norms. Therefore, both normalizable and non-normalizable terms appear in media discourse. Terms that become normalized enrich the lexical and terminological resources of the native language, largely due to the massifying function of the press. Such terms usually carry socio-political, cultural, or informational content. In contrast, non-normalizable terms are used temporarily and later disappear. Not all less popular terms are merely fashionable; some belong to specialized fields where widespread use is unnecessary, and they remain understandable primarily to professionals within those domains.